Children with Down’s Syndrome: the meaning of the taking care in the perception of mothers’ - Holanda, Eliane Rolim de; Collet, Neusa; Costa, Solange Fátima Geraldo da (Online Brazilian Journal of Nursing, 2008)
The experience of to care of a child with Down’s Syndrome (DS) requires attention and special care and may presents different meanings to the mother. This exploratory research with qualitative approach, was carried out in the Association of Parents and Friends of Handicapped Children (Associação de Pais e Amigos dos Excepcionais - APAE) of João Pessoa – PB. The objective of this study was to investigate the mothers’ perception to the taking care of a child with DS. The sample was composed of eight mothers of children with Down’s Syndrome that were assisted at the APAE. The data were collected during the month of September of 2006, was used semi-structured interviews and the responses to the questions were analyzed using the Discourse of the Collective Subject methodology. Thus, it was possible to comprehend the investigated phenomenon from the following main ideas: maternal taking care is an experience that, initially, arises negative emotions and stress situations in daily life; maternal care represents a fight to insert the son with DS in the family and in the society of integral way and without preconceptions; maternal care is a experience of love, pleasure and pride, that reflects in the personal growth of to be mother; maternal care means the possibility to offer to the son with DS a brighter and more independent future. We can understand that the experience of to be mother of child with DS is full of conflicting feelings up to overcoming, and through discourses, we see the lack of health professionals and public policies able to contribute, unrestricted, to a more inclusive society. Key-words: Down’s Syndrome; mother-child relationship; child care.